Extraction and Characterization of Type I Collagen from Parrotfish (Scarus sordidus Forsskål, 1775) Scale solubilized with the Aid of Acetic Acid and Pepsin - Jaziri, Abdul Aziz; Shapawi, Rossita; Mokhtar, Ruzaidi Azli Mohd; Noordin, Wan Norhana Md.; Huda, Nurul (International Journal of Biomaterials, 2023)
Waste from marine fish processing is an important source of valuable products. Fish collagen is considered a alternative biomaterial due to its excellent properties, and it is widely used for industrial purposes. Thus, this present study aimed to characterize acid and pepsin-soluble collagens from the waste of parrotfish (Scarus sordidus Forsskål, 1775) scales. The yields (p > 0.05) of acid-soluble collagen (ASC-PFS) and pepsin-soluble collagen (PSC-PFS) were 1.17 g/100 g and 1.00 g/100 g, respectively. Both collagen samples were categorized as type I owing to the presence of two alpha chain subunits (α1 and α1) after being confirmed by a sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE). Under the fourier transform infrared (FTIR) test, the triple helical structure of type I collagens from the ASC-PFS and PSC-PFS was maintained. Moreover, the study of UV visible spectra and X-ray diffraction (XRD) showed the similarity of collagens derived from different fish species, and the thermostability (Tmax) evaluation of all extracted collagens was in the range of 36.22–37.78°C, and their values were comparable to previous research on the fish scale collagens. The effect of various pH and sodium chloride (NaCl) treatments on solubility exhibited that the ASC-PFS and PSC-PFS were highly soluble in an acidic condition (pH < 5.0) and low concentration of sodium chloride (<30 g/L). Taken together, collagens extracted from parrotfish scale waste can be an alternative source for industries.